A novel approach on microencapsulation in drug delivery system for cancer diagnosis - Surabhi Mandal; Sourav Mohanto; Shubhrajit Mantry; Sudip Das; Shreyasi Datta; Moumita Ghosh (International Journal of Pharmacy and Analytical Research, 2022)
The main objective of this article was to discuss on microencapsulation in drug delivery system for cancer diagnosis. Microencapsulation is a process by which solids, liquids or even gases may be enclosed in microscopic particles formation of thin coatings of wall material around the substances. To obtain maximum therapeutic efficacy, it becomes necessary to deliver the agent to the target tissue in the optimal amount in the right period of time there by causing little toxicity and minimal side effects. The reasons for microencapsulation are countless. It is mainly used to increase the stability and life of the product being encapsulated, facilitate the manipulation of the product and control its liberation in an adequate time and space. In some cases, the core must be isolated from its surroundings, as in isolating vitamins from the deteriorating effects of oxygen, retarding evaporation of a volatile core, improving the handling properties of a sticky material, or isolating a reactive core from chemical attack. In other cases, the objective is not to isolate the core completely but to control the rate at which it leaves the microcapsule, as in the controlled release of drugs or pesticides. For over a half a century now, microencapsulation and encapsulated products have played a very important role in numerous industries like agriculture, chemical, pharmaceutical, cosmetic and the food industry.